CANVAS BUSINESS MODEL ESTABLISHED BY THE BALI PETRO JAYA COMPANY DURING COVID-19 - Lestara Permana, Gusi Putu; Andana, Made Garin (Jurnal Ilmiah Manajemen & Bisnis, 2021)
Business Model Analysis and Canvas Business Model Established By The Bali Petro Jaya Company During Covid-19. The Covid-19 pandemic has an impact not only in the health sector but also in the economic sector, one of which is tourism. With the limitation of community activities, the decrease in tourist visits to Bali has forced various businesses that rely on the tourism sector to close their business activities. Bali Petro Jaya, as a gas distributor for hotels and restaurants, also felt the impact. However, these companies were able to survive with the strategies they made in accordance with the existing situation. Therefore, this study aims to determine what strategies Bali Petro Jaya used during Covid-19 using the Canvas Business Model. This study used a qualitative descriptive method using semi-structured interview techniques. The result of Canvas Business Model, The company changed its business field from being originally an LPG Gas Agent with a target of hotel and restaurant consumers to become a rice distributor and selling food online to several grocery stores, rice shops, and also traditional markets after a decline in LPG sales and seeing what consumers need during the Covid-19 pandemic namely selling rice and food online. The strategy of coming directly to targeted consumers is very effective in getting new customers. This is because consumers can see examples of goods carried by the company and can also negotiate prices directly. Powering prices and using personal assistance to strengthen relationships with customers make customers feel comfortable and trust the company because a sense